How to deal with the risks of phasing out coal in Germany through national carbon pricing - Sebastian Osorio; Robert Carl Pietzcker; Michael Pahle; Ottmar Edenhofer (ZBW – Leibniz Information Centre for Economics, 2018)
Germany has an ambitious climate target for 2030 that cannot be achieved without reducing the high share of coal in power generation. In the face of this, the country has set up a commission to phase out coal. A UK-style carbon price floor is one of the options being considered. Yet implementing such a policy comes with important risks related to the following two aspects: (1) the price level necessary to reduce emissions to reach the 2030 climate target; and (2) the waterbed effect that arises from such a policy under the EU Emissions Trading Scheme (ETS) cap. In this paper, we quantify these risks using the numerical electricity market model LIMES-EU, and consider their implications as well as different options for dealing with them. Our results show that under baseline assumptions a carbon price floor of around 33 exteuro/tCO2 would be sufficient to reach the 2030 target. Under unfavourable conditions, an appropriate price floor may be nearly twice as high (57 exteuro/tCO2). The waterbed effect and related risks for the EU ETS could be reduced substantially in the mid-term (2030) through the recently introduced cancellation of allowances through the Market Stability Reserve (MSR), or through a larger coalition of countries. Germany could even fully alleviate the waterbed effect by cancelling 1.1 GtCO2 of certificates. In the long-term (until 2050), emission reductions leading up to 2030 would be almost completely (91%) offset at the EU level. Accordingly, it is essential that the national price initiates a policy sequence that leads to the EU level.
Keywords: L94; Q58; 330; EU ETS; carbon price floor; carbon price; coal phase-out; interaction; waterbed effect